Extreme events in armed conflicts: a perspective - Neuman, Yair (Frontiers in Physics, 2025)
Armed conflicts are characterized by changes in the number of fatalities that may span different orders of magnitude. A change in fatalities, crossing an order of magnitude, may be accompanied by surprise. The paper suggests estimating the probability of extreme changes in fatality (i.e., the surprise) using a physics-informed approach. More specifically, the paper aims to estimate the probability of an unseen event where the increase in the death toll crosses an order of magnitude. The perspective is presented and illustrated with a single case: the postmortem analysis of the 7 October 2023 attack on Israel.